A Novel Transmission Lines ATC Assessment Method by Considering the Generation Dispatch Limit (GDL) and Renewable Generation Capacity with Power Flow Sensitivity Analysis - Chaisit Wannoi; Narumon Wannoi; Churirut Boonkhun; Chivalai Temiyasathit; Chai Chompoo-inwai (My University, 2019)
This paper presents a novel transmission line's Availability Transfer Capability (ATC) assessment method by considering the Generation Dispatch Limit (GDL) and renewable generation capacity.This method has calculated the power remaining from the Total Transfer Capability (TTC).The TTC in this study is the total generation available declaration of all maximum Generation Shift Factor (GSF) generations to transfer power on transmission line depended on the Power Purchase Agreement of each power generation and of each renewable generation integrated in the system.The maximum GSF generations are defined by using the power sensitivity analysis.Results of this novel method are compared with the traditional transmission line's thermal limit method.Main findings showed that newly proposed method for ATC calculation can be used for the ATC assessment of transmission line and can be a good predictive index to protect power system's voltage stability issue.Moreover, it can be applied to the congestion management scheme with the optimal primary respond generation to control the stability of power transfer on the transmission line.
Keywords: Power transmission; Automatic Generation Control; Power System Optimization and Stability